Practice of electron microscopy on nanoparticles sensitive to radiation damage: CsPbBr3 nanocrystals as a case study - Duong, Tuan M.; Sharma, Kshipra; Agnese, Fabio; Rouviere, Jean-Luc; Okuno, Hanako; Pouget, Stéphanie; Reiss, Peter; Ling, Wai Li (Frontiers in Chemistry, 2022)
In-depth and reliable characterization of advanced nanoparticles is crucial for revealing the origin of their unique features and for designing novel functional materials with tailored properties. Due to their small size, characterization beyond nanometric resolution, notably, by transmission electron microscopy (TEM) and associated techniques, is essential to provide meaningful information. Nevertheless, nanoparticles, especially those containing volatile elements or organic components, are sensitive to radiation damage. Here, using CsPbBr3 perovskite nanocrystals as an example, strategies to preserve the native structure of radiation-sensitive nanocrystals in high-resolution electron microscopy studies are presented. Atomic-resolution images obtained using graphene support films allow for a clear comparison with simulation results, showing that most CsPbBr3 nanocrystals are orthorhombic. Low-dose TEM reveals faceted nanocrystals with no in situ formed Pb crystallites, a feature observed in previous TEM studies that has been attributed to radiation damage. Cryo-electron microscopy further delays observable effects of radiation damage. Powder electron diffraction with a hybrid pixel direct electron detector confirms the domination of orthorhombic crystals. These results emphasize the importance of optimizing TEM grid preparation and of exploiting data collection strategies that impart minimum electron dose for revealing the true structure of radiation-sensitive nanocrystals.